2017
DOI: 10.24815/jpsi.v5i2.9817
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kesulitan Guru Dalam Merancang Rencana Pelaksanaan Pembelajaran Mata Pelajaran Fisika Berdasarkan Kurikulum 2013 Di Kota Banda Aceh

Abstract: ABSTRAK Penelitian ini bertujuan untuk mengetahui kesesuaian RPP guru fisika se-Kota Banda Aceh dengan tuntutan kurikulum 2013 dan menganalisis kesulitan yang dihadapi oleh guru dalam menyusun RPP. Penelitian ini merupakan penelitian deskripsi kualitatif. Objek penelitian ini adalah RPP yang telah disusun oleh guru. Data diperoleh melalui studi dokumentasi, angket dan wawancara. Hasil penelitian menunjukkan bahwa skor rerata telaah RPP adalah 68,4. Skor tersebut berada pada kategori kurang. Ada beberapa catata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 2 publications
(2 reference statements)
1
11
0
6
Order By: Relevance
“…Another part that also needs to be considered the accuracy of the teacher in writing, copying, or placing the lesson plans to be used, for instance the suitability between parts of the lesson plans that are not related. This is in line with research by Ernawati & Safitri (2017) revealed that senior teachers (experience> 20 years) are more focused on concepts that tend to cause misconceptions and are difficult to understand, but are more flexible in using teaching strategies tailored to the conditions of students. In contrast to junior teachers (<10 years experience), they focus more on the depth of the material and the learning models used so they tend to be less flexible because they are more related to the planning that has been made.…”
Section: Product Evaluationsupporting
confidence: 89%
“…Another part that also needs to be considered the accuracy of the teacher in writing, copying, or placing the lesson plans to be used, for instance the suitability between parts of the lesson plans that are not related. This is in line with research by Ernawati & Safitri (2017) revealed that senior teachers (experience> 20 years) are more focused on concepts that tend to cause misconceptions and are difficult to understand, but are more flexible in using teaching strategies tailored to the conditions of students. In contrast to junior teachers (<10 years experience), they focus more on the depth of the material and the learning models used so they tend to be less flexible because they are more related to the planning that has been made.…”
Section: Product Evaluationsupporting
confidence: 89%
“…Selain itu, pendidik masih salah dalam memilih kata kerja operasional untuk kompetensi dasar, indikator dan tujuan pembelajaran. Ketika seorang pendidik belum mampu menggunakan kata kerja operasional yang sesuai dengan kompetensi yang dapat diukur maka akan berdampak pada tujuan pembelajaran berbasis HOTS (Ernawati & Safitri, 2017).…”
Section: Hasil Dan Pembahasanunclassified
“…Pelaksanaan metode drill juga memiliki kelemahan jika siswa terjebak bosan dengan latihan yang berulang-ulang tanpa ada media atau variasi kegiatan latihan (Annas, 2014). Oleh karena itu dalam pembelajaran juga memerlukan media untuk meningkatkan minat belajar siswa agar terhindar dari kebosanan (Ernawati & Safitri, 2018). Guru juga perlu menyiapkan pembelajaran dengan baik karena hal ini dapat mempengaruhi hasil belajar siswa (Abrory & Kartowagiran, 2014;Niwaz et al, 2016).…”
Section: Pendahuluanunclassified